World Bank Access to Information Annual Report FY2014 : Moving Forward Transparency and Accountability - World Bank (Washington, DC, 2015)
July 1, 2013, marked the beginning of World Bank's fourth year of implementing its Policy on Access to Information (AI Policy). In this fourth year, covering the period of July 1, 2013 through June 30, 2014 (hereinafter FY 2014), the World Bank continued its efforts to maximize the public's access to Information in the World Bank's possession and to encourage, through its own activities, improved aid transparency across the development community.